Se celebro el primero de octubre del 2023, el día del pasillo ecuatoriano - Aviles Quijano, Jaime Eduardo (2023)
Ecuadorian Pasillo Day is a celebration related to Pasillo, a traditional musical genre from Ecuador. This date is commemorated on October 1 and was established as a holiday in 1993 by executive decree during the presidency of Sixto Durán Ballén. The reason behind this date is to honor the memory of Julio Jaramillo, considered the greatest exponent of this musical genre123. On this day, the UEB Culture Department carries out various activities to remember and appreciate the hall.